Rancang Bangun Sistem Monitoring Muatan Batu Bara Menggunakan Data Logger Berbasis Mikrokontroler Esp32 pada Kapal Bulk Carrier - Bayu Setiono; Sonhaji Sonhaji; Samsul Huda (Jupiter: Publikasi Ilmu Keteknikan Industri, Teknik Elektro dan Informatika, 2025)
A conveyor is a tool with a large rubber band arranged transversely between two pulleys at a constant speed as a transporter of solid material in this case coal with the provisions of the permitted amount. Damage to the conveyor tool has a major impact on the smooth running of a coal loading and unloading process, so a coal monitoring tool was designed using an ESP32 microcontroller-based data logger. The purpose of this study is to find out how to design a coal load monitoring tool based on a data logger using the Research and Development (R&D) method type ADDIE. Using the following types of testing: static and dynamic. The research results show that the load monitoring system based on a load cell and ESP32 microcontroller demonstrates high accuracy, with a reading deviation of less than 2% from the actual weight. The system is also considered effective, as it can detect loads, adjust the hatch door angle, and transmit data to Google Spreadsheet in real-time without disruptions. Its ability to adapt to varying loads indicates that the prototype operates stably, responsively, and in accordance with the design objectives.